A Double Deprotonation Strategy for Cascade Annulations of Palladium–Trimethylenemethanes and Morita–Baylis–Hillman Carbonates to Construct Bicyclo[3.1.0]hexane Frameworks. (11th May 2021) - Yang, Zhen‐Hong; Chen, Peng; Chen, Zhi‐Chao; Chen, Zhi; Du, Wei; Chen, Ying‐Chun
Abstract: Here we report that the chemoselective activation of Tsuji's 2‐(cyanomethyl)allyl carbonates to generate the palladium–trimethylenemethane 1, 3‐dipoles via a deprotonation strategy can be realized in the presence of Morita–Baylis–Hillman carbonates from substantial activated ketones. The following SN 2′‐addition enables the formation of new 1, 3‐dipole species having an activated alkene moiety through a second deprotonation process, which then undergo cascade [1+2]/[3+2] annulations to furnish complex bicyclic [3.1.0]hexane frameworks having three contiguous quaternary stereogenic centers with good to excellent enantioselectivity. Moreover, by using benzoyl aldehyde‐derived substrates, a [1+4]/[3+2] annulation sequence is similarly developed to produce fused cyclopenta[b]furan architectures. Abstract : The palladium–trimethylenemethane 1, 3‐dipoles can be chemoseletively generated from 2‐(cyanomethyl)allyl carbonates via a deprotonation strategy, which allows the SN 2′‐addition to Morita–Baylis–Hillman carbonates from activated ketones. Cascade [1+2]/[3+2] annulations are followed to construct enantioenriched bicyclo[3.1.0]hexane frameworks with three contiguous quaternary stereogenic centers.